Ende Island Portuguese Fort: Historical Overview of Portuguese Defense in Ende - Wati, Fatma (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The conquest of Malacca in 1511 by the Portuguese became the gateway for Portuguese trading ships to the Maluku and Banda islands in search of spices. This shipping route continued to the islands of Timor and Flores with the same mission until finally capturing important ports in the archipelago as a stepping stone to controlling the spice trade in the archipelago. The mission of spreading religious teachings was also one of the important tasks of the colonialists, and to maintain their existence they built various forts as a defense mechanism. One of the forts that was considered part of Indonesia's spice route was the Portuguese fort on Ende Island. By using a historical approach, this research is intended to reveal historical events in the context of the establishment of a fort by the Portuguese on Ende Island and examine the position of this historical site for the people of Ende Island today. In this way, it is hoped that this historical relic from the past can continue to maintain its existence as a characteristic and proof of the struggle of the Indonesian people to win the independence of their homeland.